Association of statin therapy with ventricular arrhythmias among patients with acute coronary syndrome. Issue 1 (11th March 2013) - Apiyasawat, Sirin; Sritara, Piyamitr; Ngarmukos, Tachapong; Sriratanasathavorn, Charn; Kasemsuwan, Piya
Abstract : Background: In addition to lowering cholesterol, statins stabilise atherosclerotic plaques and can potentially reduce the incidence of ventricular arrhythmias. We tested the hypothesis that prior statin therapy is associated with a lower incidence of inhospital ventricular arrhythmias among patients with acute coronary syndrome (ACS). Methods: The study population consisted of 2007 patients (mean age 64 years, 67.5% male) enrolled in the Thai Registry of Acute Coronary Syndrome, a prospective, multicentre, nationwide, observational study of patients with ACS. Patients were categorised as either statin users or non-users according to their reports of statin use before enrolment at their initial presentation. The primary endpoint was inhospital ventricular arrhythmias. The secondary endpoint was a composite endpoint of inhospital ventricular arrhythmias or inhospital cardiac death. A propensity-adjusted multivariate model was developed to assess the effects of statin use on the primary and secondary endpoints. Results: During a mean hospital stay of 7 days, a total of 96 patients (4.8%) died; 82 (4.1%) of the deaths were due to cardiac causes. The primary and secondary endpoints were reached in 163 patients (8.1%) and 194 patients (9.7%), respectively. A total of 525 patients (26.2%) had used statins prior to hospitalisation. After adjusting for the propensity scores and other relevant covariates, statin use was associated with lower risks of the primary (adjusted OR 0.505, 95% CI 0.276 to 0.923) and secondary endpoints (adjusted OR 0.498, 95% CI 0.276 to 0.897). Conclusions: The use of statins is associated with a reduced incidence of ventricular arrhythmias among patients with ACS.